Penhora de percentual do faturamento de empresa devedora na execução por quantia certa contra devedor solvente: uma leitura com base no princípio da efetividade do processo - Medeiros Neto, Elias Marques de (2014)
Based on the principle of the effectiveness of the process, this thesis proposes a new analysis of the seizure of the gross revenue of the company in the civil execution proceeding against debtor solvent; in order to sustain that, provided that this attachment must be carefully applied, this kind of seizure does not need to be exceptional and may provide good results, based on the principle of proportionality, to the creditor, as to the debtor. The thesis analyses the concept of effectiveness of the process and its relation with the principles of efficiency, of reasonable duration of the process, of the due process of law, of access to justice and of proportionality. In this context, concern with the procedural effectiveness, the thesis provides an overview of the main legislative reforms that occurred after the validity of the Civil Procedure Code of 1973. In a second moment, the thesis analyses the concepts and the main principles of the civil execution proceeding and civil execution proceeding against debtor solvent, presenting the challenges and concerns to obtain an effective proceeding. The thesis provides an overview of the last and main legislative reforms that occurred in Brazil related to civil execution proceeding. In a third time, the thesis presents a new analysis regarding to the seizure of the gross revenue of the company in the civil execution proceeding against debtor solvent, based on the concept of procedural effectiveness